2017
DOI: 10.3389/fphys.2017.00472
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hepatocellular Carcinoma Metastasis Glycobiomarkers Using Advanced Quantitative N-glycoproteome Analysis

Abstract: Hepatocelluar carcinoma (HCC) is one of the most common malignant tumors with high incidence of metastasis. Glycosylation is involved in fundamental molecular and cell biology process occurring in cancer including metastasis formation. In this study, lectin microarray, lectin blotting, lectin affinity chromatography and tandem 18O stable isotope labeling coupled with liquid chromatography-mass spectrometer (LC-MS) analysis were applied to quantify the changes in N-glycosite occupancy for HCC metastasis serum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…The relative quantification of the N-glycan species that constitute the sugar shell of circulating proteins is a wealthy source of reliable biomarkers. The characterization of circulating N-glycans from sera or plasma, hereafter referred as glycomics, has provided markers in several clinical fields such as hepatology ( 247 249 ), type 2 diabetes ( 250 254 ), RA ( 255 258 ), and cancer ( 259 262 ).…”
Section: Markers Of Biological Agementioning
confidence: 99%
“…The relative quantification of the N-glycan species that constitute the sugar shell of circulating proteins is a wealthy source of reliable biomarkers. The characterization of circulating N-glycans from sera or plasma, hereafter referred as glycomics, has provided markers in several clinical fields such as hepatology ( 247 249 ), type 2 diabetes ( 250 254 ), RA ( 255 258 ), and cancer ( 259 262 ).…”
Section: Markers Of Biological Agementioning
confidence: 99%
“…Protein glycosylation, an enzymatic process by which saccharide groups are added to the maturing proteins, is involved in fundamental molecular and cell biology processes occurring in cancer, including metastasis formation. It has also been established that especially the N-glycosite occupancy of a protein is associated with the enzymatic activity and the physical stability of glycoproteins [47], which might contribute to the metastasis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…As PHA−E levels showed a significant decrease in HCC patients with early HE, they concluded that 26 PHA−E‐associated glycoproteins might be involved in the occurrence of early HE . In another study by Liu et al., 11 PHA−L reactive glycoproteins with a significantly altered N ‐glycosite occupancy (β1,6‐GlcNAc branched N ‐glycan) were identified in HCC patients with metastasis, using a lectin microarray, lectin affinity chromatography, and stable isotope labeling coupled with LC‐MS, which suggested their involvement in HCC metastasis (Table ) …”
Section: Application Of Lectin Microarrays For Biomarker Discoverymentioning
confidence: 97%